Home not alone : transition from hospital to home nutrition care, what to consider? - Eliza Mei Fransisco (World Nutrition Journal, 2023)
Malnutrition is said to be the â€œskeleton in the hospital closetâ€, mainly because it is overlooked undiagnosed, and untreated. This applies to the â€œhome closetâ€ as well, often being forgotten in the discharge planning and transition from hospital to home. Family physicians are well-qualified to provide home health care since this requires continuing and comprehensive management in a family context. It is the family physician that can initiate the decision to transition to home care, and is directly involved in the planning and coordination of the services.